2021
DOI: 10.21608/mjvh.2021.158276
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Occult Hepatitis B Virus Infection among Egyptian Blood Donors.

Abstract: Background: Although sensitive screening assays for hepatitis B virus surface antigen (HBsAg) are available, special cases of post-transfusion hepatitis B virus infection still occur. The present study was conducted to evaluate the prevalence of anti-hepatitis B core (anti-HBc) positivity and the presence of HBV-DNA in serum samples of healthy blood donors negative for both HBsAg and anti-HCV antibodies in Benha, Egypt. Materials and methods: The study included a screening of 450 selected blood donors. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In this systematic review, the estimated residual risk for HBV in sub-Saharan Africa (5913 per 1,000,000 donations) was 5 times higher than in other Southern countries (1048.4 per 1,000,000 donations). This observation was also reported in other African countries [28,26,29]. These residual risk rates in our study were significantly higher than those reported in others developing countries [11,30].…”
Section: Discussionsupporting
confidence: 75%
“…In this systematic review, the estimated residual risk for HBV in sub-Saharan Africa (5913 per 1,000,000 donations) was 5 times higher than in other Southern countries (1048.4 per 1,000,000 donations). This observation was also reported in other African countries [28,26,29]. These residual risk rates in our study were significantly higher than those reported in others developing countries [11,30].…”
Section: Discussionsupporting
confidence: 75%